Paciente masculino de 19 años de edad con síndrome de Down presenta diabetes mellitus tipo 1 y obesidad. - Moran Macías, Susana Yamiletsy (2021)
This clinical case corresponds to the study of a 19-year-old patient with Down Syndrome who has Type 1 Diabetes Mellitus, seizure syndrome, metabolic syndrome: obesity, ancanthosis nigricans, dyslipidemia. The objective of the study was to improve its nutritional condition and metabolic status through comprehensive nutritional care, aimed at controlling and solving its morbid processes. Nutritional assessment was performed through: anthropometry, biochemistry, food consumption, clinical signs, nutrient drug interaction. Nutritional assessment is possible to determine: obesity, low size, poor metabolic control, dyslipidemia, excessive food consumption and sedentary lifestyle. A calorie-controlled nutritional intervention and macronutrient intervention plan is proposed aimed at controlling your metabolic condition, weight management, considering the interactions between the drugs you consume and food; and establish healthy eating patterns, supported by caregivers.